EFFECTS OF AGE ON TWO DIFFERENT SPAN TASKS - Elosúa de Juan, María Rosa; Rato, F.; Lechuga, M.T. (Anales de Psicología / Annals of Psychology, 1998)
The aim of this paper is to investigate the effect of age on a demanding working memory task, as it is using the running memory task, in three different groups aged 18-22, 65-75 and 80-90 respectively. Morris and Jones (1990) claimed that in this task it can be assumed that the updating component requires central executive resources but not the phonological loop. Conversely, the serial recall component of the task requires the phonological loop but not the central executive. The focus of this study was to investigate whether there were effects of age on the updating performance only and / or on the serial recall performance. In order to have another measure from the serial recall a classical letter span task was also used with the same material. In the running memory task lists of 6 to 12 consonants were presented and subjects had to recall the last six items. Results indicated that there were significant differences between the three groups in the letter span task and that age interacted with list length and serial position in the running memory task. It was concluded that results from both tasks suggested that elderly subjects’ capacities were impaired.